Quality of educational and pedagogical services and evaluation of job satisfaction. Educational institution No. 7037, Ariosto Matellini Espinoza, Lima - Valdivia de Yrrarazabal, Sonia Fernanda Grados (2025)
The study titled Quality of Pedagogical Educational Service and Job Satisfaction of Teaching Staff at Educational Institution No. 7037 in Villa María del Triunfo arises from a general problem that posed the following question: What is the relationship between the quality of the educational pedagogical service and the job satisfaction of the teaching staff at this institution? The objective was also to describe whether there is a connection between the quality of pedagogical management and the job satisfaction of the teaching staff. This research has a quantitative approach, is of a descriptive correlational type, and its design is non-experimental, with a cross-sectional focus. The sample consisted of 30 teachers. To collect data, the survey technique focused on the quality of pedagogical management was employed, and an instrument designed to measure the variables of pedagogical management quality and job satisfaction was used. Additionally, the instrument validation process was carried out using Cronbach's alpha, achieving a reliability of 0.912. The data were analyzed using SPSS version 25 software. The results were obtained through this same program. It is concluded that there is a significant relationship between the quality of pedagogical management and the teaching staff. This finding was supported by the Spearman's Rho statistical test, which showed a correlation coefficient of 0.654, indicating a moderate positive correlation between pedagogical management and teacher job satisfaction; moreover, the p-value (level of significance) is 0.000.